Penerapan dan Relevansi Hukum Adat dalam Konteks Modern - Robby Nurtresna; Sopiyati Sopiyati; Ogi Charis M. Arifin; Faiq Faiq; Anisa Nurul Hidayah; Rizka Sepriyanti; Asep Guntur; Tryola Nadia (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Customary law is a legal system formed from the traditions and customs of local communities, which has evolved over centuries and become an integral part of the cultural identity of these communities. In the modern context, customary law faces significant challenges to remain relevant amidst the currents of globalization and the dominance of national law. This article explores the application and relevance of customary law in the contemporary era with a focus on case studies in several regions of Indonesia. This research employs qualitative methods with a hermeneutic approach to analyze data obtained from in-depth interviews with community leaders, academics, and legal practitioners. The findings indicate that customary law still plays a crucial role in dispute resolution and the maintenance of cultural identity in local communities. However, there are significant challenges related to harmonizing customary law with national law, especially regarding human rights protection and gender equality. This article also discusses efforts made by various stakeholders to sustain and develop customary law to be in line with contemporary developments, including formal recognition within the national legal system. In conclusion, customary law has great potential to contribute to the development of a more inclusive and diverse legal system, provided there is a commitment to addressing existing barrier.